Penerapan Sistem Programmable Logic Controler (PLC) untuk Monitoring Kualitas Air Limbah Laboratorium Kimia Hasil Pengolahan - Saputra, Deny; Yusuf, Muhammad; Adawiah, Adawiah; Rosalina, Khoerunissa Novianti (Jurnal Informatika Universitas Pamulang, 2025)
Chemical laboratory wastewater contains hazardous compounds such as carcinogenic, toxic, and difficult-to-degrade substances, which can have a negative impact on the environment and human health. Therefore, the wastewater needs to be treated first before being discharged into the environment through the Waste Water Treatment Plant (WWTP) system. This research aims to develop and evaluate a Programmable Logic Controller (PLC)-based automatic wastewater quality monitoring system, focusing on two main parameters, namely pH value and turbidity. The system utilizes a pH sensor (SKU: SEN0161) and a turbidity sensor (SEN0189), whose measurement results are displayed in real-time through a Human Machine Interface (HMI). The main contribution of this research is the implementation of a PLC-based automatic monitoring system integrated with environmental sensors and HMI, which has been proven to replace manual laboratory testing more efficiently. The test results showed that the pH value of the treated wastewater was 6.00, in accordance with the quality standards of Permen LHK No. 68 of 2016 (range 6-9). The turbidity value was recorded at 27 NTU, close to the threshold set by Permenkes No. 32 Year 2017, which is a maximum of 25 NTU. Although the turbidity result slightly exceeds the threshold, the system still provides accurate and fast detection. A comparison with laboratory results showed that the PLC-based system provided results that were not significantly different quantitatively but more efficient in terms of response time and continuous monitoring. The system has the potential to be widely applied in laboratory wastewater management, which requires continuous and automated monitoring.